NURSING RESEARCH IN GERONTOLOGY - Hammerschmidt, Karina S. de Almeida (2007)
This text is about bibliographic research with theoretical reflections about nursing research in gerontology. It aimed toidentify the scientific nursing production on gerontology. The searches were performed at LILACS; MedLINE and SciELO databases. Theresearch period was from January 1996 to January 2006. The results included 28 publications, 20 classified as research and 8 as reflections. Among the publications, 26 were articles and 2 were thesis; 65% were in English and 72% were released after the year 2000. After analysiswe propose five categories: 1) Geriatrics and gerontology in graduation; 2) Gerontology practice; 3) Functional capacity of institutionalizedelders; 4) Nursing geriatric consultation and nursing instruments used with the elderly; 5) Study/research groups in gerontology. Mostpublications focus on professional practice. These publications address elderly people’s pathologies mainly chronic diseases.